Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To determine the end behavior of the polynomial function [tex]\( f(x) = 2x^3 - 26x - 24 \)[/tex], we analyze the dominating term of the polynomial as [tex]\( x \)[/tex] becomes very large positively ([tex]\( x \rightarrow \infty \)[/tex]) and very large negatively ([tex]\( x \rightarrow -\infty \)[/tex]).
### Analyzing as [tex]\( x \to \infty \)[/tex]:
1. The leading term of the polynomial is [tex]\( 2x^3 \)[/tex].
2. As [tex]\( x \to \infty \)[/tex], the term [tex]\( 2x^3 \)[/tex] dominates all other terms.
3. Since [tex]\( 2x^3 \)[/tex] grows very large and positive as [tex]\( x \to \infty \)[/tex] (because the coefficient 2 is positive), [tex]\( f(x) \to \infty \)[/tex] as [tex]\( x \to \infty \)[/tex].
### Analyzing as [tex]\( x \to -\infty \)[/tex]:
1. Again, consider the leading term [tex]\( 2x^3 \)[/tex].
2. As [tex]\( x \to -\infty \)[/tex], [tex]\( (-x)^3 = -x^3 \)[/tex] becomes very large and negative.
3. So [tex]\( 2(-x^3) = -2x^3 \)[/tex] also grows very large and negative as [tex]\( x \to -\infty \)[/tex], which means [tex]\( f(x) \to -\infty \)[/tex] as [tex]\( x \to -\infty \)[/tex].
Given these analyses, we conclude:
- As [tex]\( x \to \infty \)[/tex], [tex]\( y \to \infty \)[/tex].
- As [tex]\( x \to -\infty \)[/tex], [tex]\( y \to -\infty \)[/tex].
Therefore, the correct description for the end behavior of the polynomial [tex]\( f(x) = 2x^3 - 26x - 24 \)[/tex] is:
- As [tex]\( x \rightarrow -\infty, y \rightarrow -\infty \)[/tex] and as [tex]\( x \rightarrow \infty, y \rightarrow \infty \)[/tex].
Thus, the answer aligns with the second given option:
- As [tex]\( x \rightarrow -\infty, y \rightarrow -\infty \)[/tex] and as [tex]\( x \rightarrow \infty, y \rightarrow \infty \)[/tex].
### Analyzing as [tex]\( x \to \infty \)[/tex]:
1. The leading term of the polynomial is [tex]\( 2x^3 \)[/tex].
2. As [tex]\( x \to \infty \)[/tex], the term [tex]\( 2x^3 \)[/tex] dominates all other terms.
3. Since [tex]\( 2x^3 \)[/tex] grows very large and positive as [tex]\( x \to \infty \)[/tex] (because the coefficient 2 is positive), [tex]\( f(x) \to \infty \)[/tex] as [tex]\( x \to \infty \)[/tex].
### Analyzing as [tex]\( x \to -\infty \)[/tex]:
1. Again, consider the leading term [tex]\( 2x^3 \)[/tex].
2. As [tex]\( x \to -\infty \)[/tex], [tex]\( (-x)^3 = -x^3 \)[/tex] becomes very large and negative.
3. So [tex]\( 2(-x^3) = -2x^3 \)[/tex] also grows very large and negative as [tex]\( x \to -\infty \)[/tex], which means [tex]\( f(x) \to -\infty \)[/tex] as [tex]\( x \to -\infty \)[/tex].
Given these analyses, we conclude:
- As [tex]\( x \to \infty \)[/tex], [tex]\( y \to \infty \)[/tex].
- As [tex]\( x \to -\infty \)[/tex], [tex]\( y \to -\infty \)[/tex].
Therefore, the correct description for the end behavior of the polynomial [tex]\( f(x) = 2x^3 - 26x - 24 \)[/tex] is:
- As [tex]\( x \rightarrow -\infty, y \rightarrow -\infty \)[/tex] and as [tex]\( x \rightarrow \infty, y \rightarrow \infty \)[/tex].
Thus, the answer aligns with the second given option:
- As [tex]\( x \rightarrow -\infty, y \rightarrow -\infty \)[/tex] and as [tex]\( x \rightarrow \infty, y \rightarrow \infty \)[/tex].
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.